Sulfur Polymers Meet Poly(ionic liquid)s: Bringing New Properties to Both Polymer Families. Issue 21 (10th September 2018) - Gomez, Iñaki; De Anastro, Asier Fdz; Leonet, Olatz; Blazquez, Jose Alberto; Grande, Hans‐Jürgen; Pyun, Jeffrey; Mecerreyes, David
Abstract: Sulfur‐containing polymers and poly(ionic liquid)s are emerging macromolecules with unique properties and applications. This article shows the first integration of these two polymer families, leading to materials with a unique combination of properties. The synthetic strategy toward sulfur‐containing poly(ionic liquid)s involves first the copolymerization of elemental sulfur with 4‐vinylbenzyl chloride and subsequent quaternization of the alkyl chloride group using N ‐methyl imidazole. The synthetic pathway is completed by the anion exchange reaction of the poly(sulfur‐ co ‐4‐vinylbenzyl imidazolium chloride) by a sulphonamide anion. The obtained polymers are fully characterized by NMR, FTIR, SEC, DSC, and TGA. The sulfur poly(ionic liquid)s combine some properties related to its poly(ionic liquid) nature, such as anion‐dependent solubility (water vs organic solvents) and high ionic conductivity as well as properties related to its sulfur content, such as redox activity. Abstract : Sulfur‐containing polymers and poly(ionic liquid)s are emerging macromolecules with unique properties and applications. This article presents the first integration of these two polymer families, leading to sulfur poly(ionic liquid)s with a unique combination of properties such as tuneable solubility, ionic conductivity, and redox properties.